A Conceptual Paper: Factors Affecting the Stability of Islamic Banking - Pungky Lela Saputri; Aisyah Dinda Saphira; Rifqi Solahuddin; Hasna Khairunnisa Salsabila; Laila Tsania Labiba (Universitas Darussalam Gontor, 2024)
This article aims to build a conceptual framework. The main objective of this study is to develop a literature review of the factors that affect the stability of Islamic banking in the GCC countries. The factors used in assessing the stability of Islamic banking are efficiency and financing risk. Islamic banks can obtain stability by managing their costs to remain efficient. By maintaining the stability of Islamic banks, the intermediation function and Islamic banking services can run optimally to contribute to economic growth. This article uses a qualitative approach and the data used is secondary data sourced from literature, books, and research journals. The result of this article is the establishment of a conceptual framework regarding how to maintain the stability of Islamic banking in GCC countries. It is expected that future research will be able to use a quantitative approach with Data Envelopment Analysis (DEA) that can help get the results of efficient and inefficient levels of providing research recommendations. Keywords: Islamic Bank, Stability, Efficiency, Financing Risk